Práticas de gestão de processos e de cultura de segurança em serviços de radioterapia e impactos na qualidade do cuidado e na segurança do paciente - Almeida, Lívia Silveira de (Universidade Federal de São Carlos, 2020)
In view of technological advances in radiotherapy services, a more specific control of issues related to the quality and safety of these services is necessary. Incidents in health and radiotherapy service centers have led to the need to improve internal processes and the safety culture in order to increase the quality of care and patient safety. This dissertation presents the results of a field research on the main practices of process management and safety culture adopted in radiotherapy services in the southeastern region of Brazil and their impacts on the quality of care and patient safety, considering the perception of medical physicist. The analysis of the relationship between these constructs was done through descriptive statistics and the application of Structural Equation Modeling based on covariance (CB-SEM - Covariance-Based Structural Equation Modeling). It was possible to evaluate the relationship between the constructs and impacts of process management and safety culture on the quality of care and patient safety. The results of the relationships indicated the impact of the process management and safety culture constructs on patient safety, but the impact on the quality of care was not statistically supported by the results presented in the proposed model. It can be seen that process management practices and safety culture have been used by radiotherapy services in the southeastern region of Brazil. The result demonstrates an advance of SR in relation to a search for the improvement of its processes and dissemination of management practices and attention to patient safety that goes beyond the technical quality of the equipment.
Process management practices and safety culture in radiotherapy services and impacts on quality of care and patient safety
Keywords: Gestão de processos; Cultura de segurança; Serviços de radioterapia; Qualidade do cuidado; Segurança do paciente; Process management; Safety culture; Radiotherapy services; Care quality; Patient safety; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO